2002
DOI: 10.1246/cl.2003.68
|View full text |Cite
|
Sign up to set email alerts
|

Electron Transport across Vesicle Bilayers Sensitized by Pyrenes: Design and Syntheses of Unsymmetrically Substituted Bifunctional Pyrenes Acting as Excellent Sensitizers

Abstract: An electron transport from an electron donor entrapped into inner waterpool to an electron acceptor in outer aqueous solution across vesicle bilayers was sensitized by pyrene derivatives incorporated in the vesicle walls, although the sensitizer ability was very dependent on the substituent group on the pyrenyl ring. The newly designed pyrenes having both a hydrophilic group linked by short methylene chain and a hydrophobic long alkyl group were found to act as excellent sensitizers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…7, 8 In the course of our studies on pyrene-sensitized photoreactions, 9 we found that pyrene derivatives embedded into the bilayers of phosphatidylcholine (PC) vesicles photochemically induce transport of electrons from ascorbate (Asc − ) entrapped into the inner waterpool to MV 2+ dissolved in the outer aqueous solution without any additional components acting as electron carriers. 10 The free-energy change for the total redox reaction of our electron transfer system is estimated to be +12.7 kcal mol −1 . 11,12 Thus, although the pyrenes employed in our experiments unfortunately do not absorb visible light (>400 nm), this system satisfies the other three criteria mentioned above.…”
Section: Introductionmentioning
confidence: 92%
“…7, 8 In the course of our studies on pyrene-sensitized photoreactions, 9 we found that pyrene derivatives embedded into the bilayers of phosphatidylcholine (PC) vesicles photochemically induce transport of electrons from ascorbate (Asc − ) entrapped into the inner waterpool to MV 2+ dissolved in the outer aqueous solution without any additional components acting as electron carriers. 10 The free-energy change for the total redox reaction of our electron transfer system is estimated to be +12.7 kcal mol −1 . 11,12 Thus, although the pyrenes employed in our experiments unfortunately do not absorb visible light (>400 nm), this system satisfies the other three criteria mentioned above.…”
Section: Introductionmentioning
confidence: 92%
“…In the course of our studies on artificial photosynthesis using pyrene derivatives as chromophores, , we have investigated the aggregation behaviors of amphiphilic pyrenes in water and their usefulness for artificial light-harvesting systems. Pyrenes have several merits as chromophores for studies on artificial photosynthesis: large extinction coefficients in the near-ultraviolet region, relatively long lifetime of their singlet excited state, intense fluorescence that is sensitive to their surroundings, and ease of preparation of a wide variety of their derivatives.…”
Section: Introductionmentioning
confidence: 99%